Growth of Pyrola rotundifolia ssp. maritima in relation to shade - Hunt, R; Hope-Simpson, J.F (The New phytologist, 1990)
The maritime race of the larger wintergreen [Pyrola rotundifolia L. ssp. maritima (Kenyon) E. F. Warb.] was investigated in relation to its light environment at Braunton Burrows in south-west England. Measurements made at the site of its greatest abundance indicated that, in July, Pyrola commonly experiences an irradiance which is below 10% of full daylight with some habitats providing less than 1%. The species also occurs in situations receiving up to 100% daylight; at or towards this extreme the foliage is yellowish-green instead of deep green, giving an impression of reduced luxuriance. The mean specific leaf area of plants growing in the field was found to be inversely related to mean percentage irradiance received at each site. However, the slope of this trend was slight. Detached, rooted rosettes were removed from the field and grown for 85 days in a glasshouse under treatments which provided 100, 20.2 and 6.1% daylight. The plants in all treatments appeared normal but growth was slow. Yields and relative growth rates were significantly reduced by shading (P < 0.05). The depressing effect of shading on growth rate was very slightly less than on unit leaf rate, the difference being due to slight increases in leaf area ratio. This, in turn, was tracted entirely to small increases in specific leaf area. Leaf weight ratio was not affected significantly, nor were substantial effects recorded in root/shoot ratio or in fresh weight/dry weight ratio. We conclude that the vegetative growth of Pyrola has a low capacity for adjustment to both natural and experimental shading; its growth rate in the field will tend to be lower under a dense leafy canopy than in less shaded habitats. The inherently low growth rate might, however, be an advantageous feature under shade conditions. The evident success of the species in shaded situations is certainly due to factors other than a simple shade requirement for vegetative growth.